Pengembangan Peserta Didik Berkebutuhan Khusus pada Sekolah Inklusi - Haromain, Haromain (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
This article aims to describe the school's efforts in developing basic abilities and character development of students with special needs. This research uses a qualitative method with a case study design at SD Negeri 20 Mataram. Data analysis was carried out since the data collection was carried out until the data was collected through the stages of data collection, data reduction, data exposure and drawing conclusions. The results showed that the basic abilities of students with special needs were carried out through optimizing the resource room as a learning center for ABK and optimal assistance from teachers and parents in children's learning. Character development is carried out through positive behavior habituation activities that can increase the awareness of each child to be able to live side by side with other people regardless of their background.